In situ probing and integration of single self-assembled quantum dots-in-nanowires for quantum photonics. (3rd September 2015) - Zha, Guo-Wei; Shang, Xiang-Jun; Ni, Hai-Qiao; Yu, Ying; Xu, Jian-Xing; Wei, Si-Hang; Ma, Ben; Zhang, Li-Chun; Niu, Zhi-Chuan
Abstract: The realization of fiber-output single photon sources is necessary for quantum photonics. Here we present in situ probing and integration of single self-assembled quantum dots (QDs)-in-nanowires. Single self-assembled AlGaAs QDs were synthesized in GaAs/AlGaAs core–shell nanowires by molecular beam epitaxy and characterized by optical excitation in both micro-PL and fiber-integrating set-up. Cascaded biexciton–exciton emission with a saturation signal of 1000 counts per second at nitrogen temperature is achieved through the fiber-integrating setup, which makes single mode fibers an ideal candidate for single photons sources and paves the way for the realization of 'all fiber' devices. Numerical calculations were carried out to illustrate the collection efficiency and polarized photoluminescence characteristics. Extraction efficiencies as high as 70% over a broadband emission are reported and increase by a factor of about seven in comparison with air extraction, due to the larger refractive index of the fiber core.